BDNF promoter I methylation correlates between post-mortem human peripheral and brain tissues. (February 2015) - Stenz, Ludwig; Zewdie, Seblewongel; Laforge-Escarra, Térèse; Prados, Julien; La Harpe, Romano; Dayer, Alexandre; Paoloni-Giacobino, Ariane; Perroud, Nader; Aubry, Jean-Michel
Highlights: The periphery correlates with the brain in term of BDNF promoter I methylation levels. The periphery could be used to reflect the brain for methylation in BDNF promoter I. BDNF promoters I and IV are correlated in term of methylation in the hippocampus. Males showed higher BDNF promoter I methylation levels compared to females in brain, blood and muscle tissues. Abstract: Several psychiatric disorders have been associated with CpG methylation changes in CG rich promoters of the brain-derived neurotrophic factor ( BDNF ) mainly by extracting DNA from peripheral blood cells. Whether changes in peripheral DNA methylation can be used as a proxy for brain-specific alterations remains an open question. In this study we aimed to compare DNA methylation levels in BDNF promoter regions in human blood cells, muscle and brain regions using bisulfite-pyrosequencing. We found a significant correlation between the levels of BDNF promoter I methylation measured in quadriceps and vPFC tissues extracted from the same individuals ( n = 98, Pearson, r = 0.48, p = 4.5 × 10 −7 ). In the hippocampus, BDNF promoter I and IV methylation levels were strongly correlated (Pearson, n = 37, r = 0.74, p = 1.4 × 10 −7 ). We found evidence for sex-dependent effect on BDNF promoter methylation levels in the various tissues and blood samples. Taken together, these data indicate a strong intra-individual correlation between peripheral and brain tissue. They also suggest that sex determines methylation patterns in BDNF promoter region across different types of tissue, including muscle, brain, and blood.